Evaluating the Financial Health of Islamic Banks: A CAMEL Approach at PT BPRS HIK MCI - Santosa Santosa; Agniya Thahira; Ana Rimbasari (LPPM STIE KRAKATAU, 2026)
This study aims to analyze the financial soundness of PT BPRS HIK MCI using the CAMEL framework, which comprises Capital, Asset Quality, Management, Earnings, and Liquidity, within the context of recent economic dynamics. The research employs a quantitative approach with a descriptive-analytical design. Secondary data were obtained from the financial statements of PT BPRS HIK MCI for the observed period. Data analysis was conducted by calculating financial ratios representing each CAMEL component and comparing the results with the applicable banking soundness standards. The findings indicate that the overall financial soundness of PT BPRS HIK MCI falls into the healthy category. The capital adequacy ratio reflects the bank’s ability to absorb potential risks, asset quality remains within acceptable limits, operational efficiency is relatively well maintained, profitability demonstrates positive performance, and liquidity is sufficient to support the bank’s intermediation function. These results suggest that the bank’s risk management practices and financial management have been implemented effectively. This study provides managerial implications emphasizing the importance of strengthening capital structure, improving financing quality, enhancing operational efficiency, and maintaining adaptive liquidity management to ensure the sustainability and stability of Islamic rural banks amid economic uncertainty.